THE MODERATION EFFECT OF COVID-19 ON REGIONAL INCOME OF THE PROVINCIAL GOVERNMENT IN INDONESIA - Edy Suprianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to examine the effect of Regional Income (PAD) on Capital Expenditures with Covid-19 as moderating variable. The population of this study was 136 provincial governments in Indonesia in 2019-2020. Also, this study used purposive sampling method and documentation as the data collection technique. The analysis technique used the Moderated Regression Analysis method. Based on the results of statistical tests, PAD had a significant positive effect on Capital Expenditures, but the Covid-19 had an insignificant negative effect on PAD and Capital Expenditures. Keywords: Regional Income, Capital Expenditures, Covid-19